Assessment of the Effectiveness and Efficiency of the Cadastral Survey Program of the Department of Environment and Natural Resources (DENR) - Gilberto M. Llanto; Maureen Ane D. Rosellon (Philippine Institute for Development Studies (PIDS), 2013)
The slow progress of the Cadastral Survey Program in the Philippines has been associated with implementation issues that have affected the effectiveness and efficiency of the program. A review of the processes, procedures, and existing institutional set-up in the conduct of cadastral surveys helped identify factors behind the slow progress and delays in implementation. These factors include the tedious procurement process and procedures; slow verification of survey reports/returns; peace and order situation in areas subject to cadastral survey; lack of cooperation from the local government units; and inaccurate and dated land database. The paper assessed the accomplishments of the cadastral survey program and estimated the funding requirements needed to finish the remaining surveys based on data and information made available by the Department of Environment and Natural Resources/Land Management Bureau and other government agencies. Based on the findings, recommendations on how the program may be improved were presented.
Keywords: 330; land management; Philippines; cadastral survey; boundary agreement process; land parcel; public land subdivision survey; land titling